1986
DOI: 10.1073/pnas.83.20.8002
|View full text |Cite
|
Sign up to set email alerts
|

Human striatal dopamine receptors are organized in compartments.

Abstract: Dopamine (D2) receptors visualized in postmortem human striatum by quantitative autoradiography of [3H]spiroperidol binding are organized into circumscribed zones of low receptor density separated from other such zones by regions of higher D2 density. The D2-rich zones of the caudate nucleus and putamen contain twice the binding of D2-poor zones. The Hill coefficient, obtained from saturation analysis of [3H]spiroperidol binding to thin sections of human striatum, gave a value near unity, indicating the bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 23 publications
3
36
1
2
Order By: Relevance
“…In agreement with data reported earlier (Joyce et al 1986;Murray et al 1994), the concentration of D 2 receptors was found to be highest in the rostral CN and Pu, with the sites distributed evenly through the dorsoventral extent of the striatum (Table 2 and Figure 1A). In contrast, D 3 receptors were more abundant in the NAC and ventral aspect of the rostral Pu and were concentrated in areas of dense binding giving both structures a patchy appearance (Table 2 and Figure 1B) as reported previously (Murray et al 1994;Gurevich et al 1997).…”
Section: Basal Ganglia and Basal Forebrainsupporting
confidence: 92%
“…In agreement with data reported earlier (Joyce et al 1986;Murray et al 1994), the concentration of D 2 receptors was found to be highest in the rostral CN and Pu, with the sites distributed evenly through the dorsoventral extent of the striatum (Table 2 and Figure 1A). In contrast, D 3 receptors were more abundant in the NAC and ventral aspect of the rostral Pu and were concentrated in areas of dense binding giving both structures a patchy appearance (Table 2 and Figure 1B) as reported previously (Murray et al 1994;Gurevich et al 1997).…”
Section: Basal Ganglia and Basal Forebrainsupporting
confidence: 92%
“…The D2 receptor family includes three subtypes, names D 2 , D 3 , and D 4 , (Sibley et al 1993), which exhibit distinct pharmacological properties and are concentrated in human brain in different regions (Joyce and Meador-Woodruff 1997 (Murray et al 1994); whereas [ 3 H]spiroperidol has low affinity for the D 3 receptor (Sokoloff et al 1990). It is now clear that D 2 -like receptors labeled with [ 3 H]spiroperidol (Joyce et al 1986a) have a distribution different from that of D 2 and D 3 receptors labeled with [ 125 I]epidepride in striatum. Murray et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This system enabled the autoradiographic images to be digitized, and the mean optical density of each brain region of interest was converted to a value of fmol/mg protein. For autoradiographs obtained by sections labeled with a 3 H-ligand, a standard curve for 3 H based on calibrations of low activity 3 H-plastic standards to 3 H-isoleucine-tissue mash standards was used (Joyce et al 1986a). For autoradiographs obtained by sections labeled with a 125 -ligand, standards calibrated against 125 I-tissue mash standards for the appropriate exposure time was used according to the method described by Artymyshyn et al (1990).…”
Section: Quantitative Autoradiography Studiesmentioning
confidence: 99%
“…Although a proportion of the D 1 and D 2 receptors are co-localized on the same neurons, D 1 receptors are mainly expressed in neurons in the ''direct'' striatonigral feedback pathway, whereas D 2 receptors are expressed in ''indirect'' pathways that include interneurons (Gerfen et al, 1995;Hersch et al, 1995). At a histological level, this differential organization corresponds to the observation that D 1 neurons are primarily located in striosomes, whereas D 2 neurons are preferentially found in the matrix component of the striatum (Joyce et al, 1986;Graybiel et al, 1994).…”
Section: Generality Versus Specificitymentioning
confidence: 92%